Prophylactic use of pentoxifylline and tocopherol in patients who require dental extractions after radiotherapy for cancer of the head and neck. Issue 5 (June 2016) - Patel, Vinod; Gadiwalla, Yusuf; Sassoon, Isabel; Sproat, Chris; Kwok, Jerry; McGurk, Mark
Abstract: Osteoradionecrosis (ORN) is a complication seen intermittently in patients who have had radiotherapy to the head and neck, and results of treatment with pentoxifylline and tocopherol (PVe) have been encouraging. As a consequence, some argue that this should be used prophylactically to lower the risk of ORN after dental extractions in this group. We retrospectively analysed data on 390 dental extractions in 82 patients who had had radiotherapy for cancer of the head and neck. Each had been given PVe prophylactically. Only one patient (1.2%) developed ORN (rate/tooth 0.26%). Patients had taken PVe for a mean (SD) of 11 (23) weeks preoperatively and 13.6 (18) weeks postoperatively. The incidence we found was lower than that normally associated with dental extractions in irradiated patients (7%).